PROBLEMATIKA PEMBELAJARAN PAI BERBASIS DARING PADA SISWA KELAS XI IIS PUTRI DI SMAIT NURUL ‘ILMI TENGGARONG - Asmaningrum, Novita; Riadi, Akhmad; Maryam (AZKIYA, 2022)
The existence of Corona Virus Disease 2019 (Covid-19) which is spreading in several countries around the world is currently forcing the government to issue various policies, one of which is online learning, in order to prevent the virus from spreading further. During this pandemic, many problems were found, especially learning activities, one of which was at SMA IT Nurul 'Ilmi Tenggarong. To find out the problems of online-based Islamic religious education learning in class XI IIS Putri students at SMA IT Nurul 'Ilmi Tenggarong, it is necessary to do research. The results of the study found that the problems faced by teachers were the limited time that must be used for teaching, while the demands of the material had to be conveyed to students for the achievement of mastery learning. Meanwhile, students are faced with interference or difficulty accessing the internet network for those who are in places with less affordable internet access, meanwhile, the delivery of material from teachers is limited and more in the form of assignments.